Perceptions on drug use, misuse and abuse by selected high school students - Perez, Silvina Aguelo 1941- (1976)
The objective of the study was to determine the perception on drug use, misuse and abuse by selected high school students of V. Mapa High School, Manila. The study employed the normative survey method of research. It is a method of quantitative description of the general characteristics of the group. A questionnaire checklist was used in gathering the needed data. The study concluded that V. Mapa High School students have more incorrect perceptions on drug use, misuse and abuse than correct perceptions.
"October, 1976."
Vita.
Thesis (M.A.T. Health Education)--University of the Philippines, Diliman.
Keywords: High school students -- Drug use -- Philippines -- Manila; High school students -- Philippines -- Manila -- Attitudes; Drug abuse -- Study and teaching (Secondary) -- Philippines -- Manila; Drugs -- Health aspects -- Philippines; Health attitudes -- Philippines -- Manila